N6-methyladenosine demethylase FTO targets pre-mRNAs and regulates alternative splicing and 3′-end processing. Issue 19 (30th August 2017) - Bartosovic, Marek; Molares, Helena Covelo; Gregorova, Pavlina; Hrossova, Dominika; Kudla, Grzegorz; Vanacova, Stepanka
Abstract: N6-methyladenosine (m 6 A) is the most abundant base modification found in messenger RNAs (mRNAs). The discovery of FTO as the first m 6 A mRNA demethylase established the concept of reversible RNA modification. Here, we present a comprehensive transcriptome-wide analysis of RNA demethylation and uncover FTO as a potent regulator of nuclear mRNA processing events such as alternative splicing and 3΄ end mRNA processing. We show that FTO binds preferentially to pre-mRNAs in intronic regions, in the proximity of alternatively spliced (AS) exons and poly(A) sites. FTO knockout (KO) results in substantial changes in pre-mRNA splicing with prevalence of exon skipping events. The alternative splicing effects of FTO KO anti-correlate with METTL3 knockdown suggesting the involvement of m 6 A. Besides, deletion of intronic region that contains m 6 A-linked DRACH motifs partially rescues the FTO KO phenotype in a reporter system. All together, we demonstrate that the splicing effects of FTO are dependent on the catalytic activity in vivo and are mediated by m 6 A. Our results reveal for the first time the dynamic connection between FTO RNA binding and demethylation activity that influences several mRNA processing events.